Utilización de carbapenems en el Servicio de Medicina del Hospital Regional Docente de Trujillo, enero-diciembre 2016 - Pacheco Ramos, Mauro Valdemar (2022)
The present investigation aims to evaluate the use of Carbapenems in patients hospitalized in the medical service of the Hospital Regional Docente de Trujillo January-December 2016", the indication criteria, dose, frequency, duration of treatment, safety and convenience were evaluated, for which 137 clinical histories were selected from a total of 184, to whom Carbapenems were prescribed. The data collected from the medical records are related to general data of the patients and data of clinical relevance such as main diagnosis and comorbidities, pharmacotherapy, laboratory and radiological tests, consolidating the same information that the concordance was evaluated. For concordance, the Burke A, Gilbert D, Mensa J and PAHO Guidelines were used, in addition to the sources of information to assess drug interactions. Obtaining the following results: The main diseases diagnosed with an indication for Carbapenems correspond to unspecified urinary tract infection, pneumonia due to unspecified microorganism and sepsis due to unspecified microorganism. The prescription of meropenem associated with another antibiotic, imipenem/cilastatin associated with another antibiotic, meropenem monotherapy, and imipenem/cilastatin monotherapy, correspond to 40.14%, 29.93%, 16.79%, and 13.14%, respectively. . The indications, dose, frequency of administration and duration of treatment of Carbapenems, agree with the Clinical Practice Guidelines in 71.89% as second-line therapy, 78.85%, 85% and 63.5%, respectively. 30.7% of adverse reactions to Carbapenems, the main being the increase in creatinine, 19.0% and 0.7% interactions with vancomycin and valproic acid, representing 35.8% of contraindications of Carbapenems with the groups of pathologies N, K and G. Concluding, that the use of Carbapenems has concordance in the indication parameters, dose, frequency of administration and duration of treatment between 63.5% and 85% with the Practice Guidelines Clinic under study.